Pine Resin as a Natural Polymer Binder in Pine Cone-Reinforced Lightweight Concrete - Kistak, Celal; Hassan, Araz Muhammed; Bicer, Ayse; Celik, Nevin (Mdpi, 2026)
The aim of this study is to investigate the potential applications of pine cones as plant-based waste material in the construction industry. In order to achieve this target, the pine cone particles (PCP) are mixed with cement to create new lightweight concretes. Furthermore, pine tree resin (PTR), acting as a natural bio-polymer binder, is incorporated into selected samples to ascertain its potential as a binder. The pine cones are cut into particles of 2-4 cm, 0-2 cm, and ground into a powder. A series of critical tests is conducted on the novel produced samples, including thermal conductivity, specific heat, density, compressive strength, water absorption rate, and drying rate. The experiments show that thermal conductivity, specific heat capacity, and thermal expansion coefficient decrease as the weight ratio and size of PCP increase. The presence of PTR increases porosity, further decreasing thermal conductivity, specific heat, and thermal expansion coefficients for the majority of samples. The compressive strength values decrease with the presence of PTR and PCP. Regarding durability, the water absorption ratios remain below the critical 30% threshold, making the material suitable for internal applications or external facades protected by coating/plaster or as external coverings.
Keywords: pine tree cone; pine tree resin; lightweight concrete; thermal-mechanical properties